Tissue remodeling gene expression in a murine model of chronic rhinosinusitis - Sautter, Nathan B. (2012)
OBJECTIVE/HYPOTHESIS: The Matrix Metalloproteinase (MMP), Fibroblast Growth Factor (FGF) and Bone Morphogenetic Protein (BMP) families regulate tissue remodeling in many normal and pathophysiologic processes. We hypothesize that induction of chronic sinonasal inflammation will be associated with changes in regulation of these tissue remodeling cytokines. METHODS: Balb/c mice aged 8–12 weeks were sensitized and treated with intranasal Aspergillus fumigatis (AF) three times per week for 1 week, 3 weeks, 2 months and 3 months (n=8 each time point). Sinonasal tissues were evaluated for changes in MMP, FGF and BMP regulation using standard RT-PCR techniques. Additional snouts were processed for histology and immunohistochemistry. Untreated mouse snouts of identical age were used as controls. RESULTS: Significant upregulation of MMP8 was observed at 2 months, and MMP1a, MMP7, MMP8 and MMP12 were all significantly upregulated at 3 months. FGF3 was significantly upregulated at 3 weeks and 3 months, and FGF5, FGF6 and FGF8 were all significantly upregulated at 3 months. BMP8b and BMP9 were significantly upregulated at 3 months. Histologic analysis revealed mucosal, stromal and mucin gland hypertrophy, increased mucin production, and metaplasia with loss of cilia. Antibody staining was strongly positive in the AF treated group. CONCLUSION: Induction of CRS is associated with time-dependent changes in tissue remodeling cytokine expression occurring in conjuction with inflammatory tissue changes. Antibody staining for upregulated cytokines suggests local production within the sinonasal mucosa. Further study is required to better understand the association between BMP, FGF and MMP regulation and tissue remodeling changes resulting from chronic inflammation.